EMERGENCY PREDICTION SYSTEM AND ITS PROBLEMS - Akhmadbek Jalilov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article examines the current state of emergency (E) forecasting systems and their challenges. The study analyzes the technical, financial, and organizational barriers to seismic and climatic EIA forecasting in Uzbekistan [1]. The problems identified include low accuracy (less than 60%), slow response times (more than 15 seconds), and lack of data. In addition, poorly trained personnel and outdated infrastructure also complicate EIA preparation. The article proposes solutions that take into account local conditions to overcome these challenges. Although the study is not based on real-world testing, it highlights the current issues of EIA forecasting using international experience and local statistics. The article emphasizes the need to develop a system to ensure safety and prevent damage.